Giant angioleiomyoma of uterus: A case report with focus on CT imaging - Antonio Pierro, MD; Fabio Rotondi, MD; Savino Cilla, PhD; Maria De Ninno, MD; Marilena Mattoni, MD; Stefano Berardi, MD; Marco Pericoli Ridolfini, MD; Giuseppina Sallustio, MD (Radiology Case Reports, 2018)
We report a rare case of giant angioleiomyoma located in the uterus and detected in a 37-year-old woman. The uterus is an extremely rare location for angioleiomyoma. The definitive diagnosis is usually obtained only after the histopathologic examination because the imaging criteria are challenging for this disease. We focused our attention on the main computed tomography features able to provide a robust preoperative diagnosis of this rare clinical entity. Keywords: Giant angioleiomyoma, Abdominal mass, Uterine fibroids, Sand-like enhancement